Taxonomy of the genus Protocypus J. Müller, 1923 (Coleoptera: Staphylinidae: Staphylinini) and two new species from China - He, Liang; Zhou, Hong-Zhang (Zootaxa, 2017)
Two new species of the genus Protocypus J. Müller, 1923 are described from China: Protocypus taibaiensis sp. nov. and Protocypus admirabilis sp. nov.. Line drawings and color illustrations of the adults, and the genitalia of the new species and Protocypus fulvotomentosus (Eppelsheim, 1889), Protocypus latro Smetana, 2005, Protocypus lupus Smetana, 2005, Protocypus pilifer Smetana, 2005, Protocypus wrasei Smetana, 2005 are given. A key to the Chinese species of the genus Protocypus is provided.